2016
DOI: 10.5152/iao.2016.2532
|View full text |Cite
|
Sign up to set email alerts
|

An Implantable Hearing System As Rehabilitation for Hearing Loss Due to Bilateral Aural Atresia: Surgical Technique and Audiological Results

Abstract: OBJECTIVE:To demonstrate the surgical technique and audiological results of a middle ear implant for restoring hearing in patients with bilateral aural atresia and microtia with conductive or mixed hearing loss. MATERIALS and METHODS:In this prospective study, 12 subjects aged 12 years and older presenting with hearing loss and bilateral congenital aural atresia underwent surgical insertion of a middle ear implant. The patients underwent tympanomastoidectomy with a wide opening of the attic and preservation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
3
5
0
1
Order By: Relevance
“…Mean postoperative, VSB-aided word recognition scores at 12 and 36 months resulted in 67.8 and 67.1%, respectively. Our findings are in good agreement with those from previous studies including vibroplasty couplers in which WRS at 65 dB SPL of around 70% were reported [Brito et al, 2016;Busch et al, 2016;Hüttenbrink et al, 2004;Müller et al, 2017;Schraven et al, 2016;Schwab et al, 2014;Wang et al, 2016;Zhao et al, 2016]. The treatment success in speech intelligibility is further supported by a mean SRT improvement of 22.7 dB SPL at 12 months and of 17.8 dB SPL at 36 months postoperatively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mean postoperative, VSB-aided word recognition scores at 12 and 36 months resulted in 67.8 and 67.1%, respectively. Our findings are in good agreement with those from previous studies including vibroplasty couplers in which WRS at 65 dB SPL of around 70% were reported [Brito et al, 2016;Busch et al, 2016;Hüttenbrink et al, 2004;Müller et al, 2017;Schraven et al, 2016;Schwab et al, 2014;Wang et al, 2016;Zhao et al, 2016]. The treatment success in speech intelligibility is further supported by a mean SRT improvement of 22.7 dB SPL at 12 months and of 17.8 dB SPL at 36 months postoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study the SNR significantly improved from +5.75 dB SNR in the unaided to -0.17 dB SNR in the aided condition 36 months after implantation (improvement: -5.5 dB SNR). This result goes in line with an SNR improvement of -4.33 dB SNR reported by Brito et al [2016].…”
Section: Discussionsupporting
confidence: 91%
“…A significant improvement of SNR from 10 dB ± 6.7 dB to 2 dB ± 5.4 dB (gain = 8 dB) was found in our study. This result is in line with previously reported results by Brito et al [ 20 ], who reported a short term improvement from 5.64 (SD, 4.33) to 1.31 (SD, 3.89) (gain = 4.3 dB). Since 2 dB SNR resembles the average normal performance of people without hearing impairments [ 19 ], our findings can be considered as a good result.…”
Section: Discussionsupporting
confidence: 93%
“…Based on these considerations, the HEARRING group characterized beneficial treatment as follows: speech score in quiet ≥70% [ 8 , 9 , 14 , 15 , 16 , 17 , 18 ] and wearing time ≥8 h [ 19 , 20 , 21 , 22 , 23 , 24 ], which was visualized in the HEARRING graph.…”
Section: Methodsmentioning
confidence: 99%